Changing paradigms in management of acute calculous cholecystitis - Dey, Saurav; Yadav, Rahul; Yadav, Digvijay; Jyoti, Vidur (International Surgery Journal, 2026)
Background: The term “acute calculous cholecystitis” indicates inflammation of the gall bladder caused by gallbladder stones. Usually the patients diagnosed with acute cholecystitis are advised to undergo laparoscopic cholecystectomy within 72 hours of onset of symptoms or electively after 6 to 12 weeks. Methods: This is a retrospective study carried out at Department of Minimal Access and General Surgery, Max Hospital, Gurugram, India aimed at evaluating the ideal timing for undertaking surgery for managing acute calculous cholecystitis. This study of 1004 patients was carried out from July 2022 to August 2025 after having obtained due approval from the institutional authorities. For purposes of this study we included all patients presenting to our department for management of calculous cholecystitis during the period of this study. Out of these 1004 patients, a total of 491 were diagnosed as acute calculous cholecystitis and their clinical data was analyzed deploying standard statistical tools for purposes of this research. Results: Out of the 1004 patients who underwent laparoscopic cholecystectomy from a period of July 2022 to August 2025, 491 patients were diagnosed as having acute cholecystitis. 223 patients were taken up for surgery with prior written consent within 0-3 days after getting diagnosed with symptomatic calculous cholecystitis (early surgery group). Operation for the remaining 268 patients had to be delayed for a variety of reasons which included co-morbid medical conditions besides personal preferences (delayed surgery group). Conclusions: Acute calculous cholecystitis continues to be a common surgical condition with evolving management strategies. The findings of the present study demonstrate that early laparoscopic cholecystectomy within 72 hours of the onset and also as soon as technically possible is both a safe and advantageous approach in the management of these patients.